Sustainable pressure injury prevention - Charleen Singh; Noordeen Shoqirat; Lee Thorpe; Stephanie Villaneuva (BMJ Open Quality)
The quality department used adaptive leadership and the plan-do-study-act cycle to decrease pressure injury (PI) rates. After identifying gaps, the pressure injury prevention bundle was developed and implemented to bring evidence-based nursing practice to frontline nurses. Organisational rates of PI was followed for 4 years (2019–2022) and a smaller subset of 88 patients were followed in the prospective arm. Using statistical analysis, the decrease in PI rates (90%) and severity is significant (p<0.5) and sustained compared with the year prior to interventions.